A precessing molecular jet signaling an obscured, growing supermassive black hole in NGC 1377? - S. Aalto; F. Costagliola; S. Muller; K. Sakamoto; J. S. Gallagher; K. Dasyra; K. Wada; F. Combes; S. García-Burillo; L. E. Kristensen; S. Martín; P. van der Werf; et al. (EDP Sciences, 2022)
With high resolution (0.̋25 × 0.̋18) ALMA CO 3-2 (345 GHz) observations of the nearby (D = 21 Mpc, 1'' = 102 pc), extremely radio-quiet galaxy NGC 1377, we have discovered a high-velocity, very collimated nuclear outflow which we interpret as a molecular jet with a projected length of ±150 pc. The launch region is unresolved and lies inside a radius r< 10 pc. Along the jet axis we find strong velocity reversals where the projected velocity swings from -150km s-1 to +150 km s-1. A simple model of a molecular jet precessing around an axis close to the plane of the sky can reproduce the observations. The velocity of the outflowing gas is difficult to constrain due to the velocity reversals but we estimate it to be between 240 and 850 km s-1 and the jet to precess with a period P = 0.3-1.1 Myr. The CO emission is clumpy along the jet and the total molecular mass in the high-velocity (±(60 to 150 km s-1)) gas lies between 2 × 106M⊙ (light jet) and 2 × 107M⊙(massive jet). There is also CO emission extending along the minor axis of NGC 1377. It holds > 40% of the flux in NGC 1377 and may be a slower, wide-angle molecular outflow which is partially entrained by the molecular jet. We discuss the driving mechanism of the molecular jet and suggest that it is either powered by a (faint) radio jet or by an accretion disk-wind similar to those found towards protostars. It seems unlikely that a massive jet could have been driven out by the current level of nuclear activity which should then have undergone rapid quenching. The light jet would only have expelled 10% of the inner gas and may facilitate nuclear activity instead of suppressing it. The nucleus of NGC 1377 harbours intense embedded activity and we detect emission from vibrationally excited HCN J = 4-3ν2 = 1f which is consistent with hot gas and dust. We find large columns of H2 in the centre of NGC 1377 which may be a sign of a high rate of recent gas infall. The dynamical age ofthe molecular jet is short (<1 Myr), which could imply that it is young and consistent with the notion that NGC 1377 is caught in a transient phase of its evolution. However, further studies are required to determine the age of the molecular jet, its mass and the role it is playing in the growth of the nucleus of NGC 1377.